Tinjauan Yuridis Surety Bond Pada PT. Askrindo(Studi Kasus Pada Pengadaan Barang/Jasa Di Pemerintah Kota Surakarta) - Sudibyo, Nanang; , Shalman al- farizy, S H , MM; , Inayah, SH., MH (2015)
Surety Bond is an alternative of Bank Guarantee issued by the insurance company,is intended to help employers who have good technical ability, but less supported by financial capability. Surety Bond Agreement is an additional agreement involving three parties, namely the Principal as executor of the work, the obligee as an employer, Surety Company as guarantor. The purpose of this study was to determine: (1) The process of issuance of surety bonds in PT. Askrindo on project procurement of goods/services Surakarta City Government; (2) The legal consequences that arise in the event of default in the execution of Surety Bond in PT Askrindo on project procurement of goods/services of the Government of Surakarta. This research includes empirical juridical ie an approach which refers to the rules written to then see how the implementation on the ground. The experiment was conducted at the offices of PT Askrindo of Surakarta. Source of data using secondary data Surety Bond agreement and primary data field research in the Office of PT Askrindo of Surakarta. Data were analyzed using qualitative analysis. The results showed that: (1) Surety Bond Issuance Procedures in PT. Askrindo on project procurement of goods and services in the Government of Surakarta is: create a basic agreement that contains the amount of the loss will be borne by the surety in the event of default are done Principal, apply as a customer, fill out the application form, Principal complete documents, the underwriting process (examination), PT. Askrindo then tried to obtain a picture of the risks to be borne by the analysis of five (5) C, namely: Character, Capital, Capacity, Condition, and collateral to the principal conditions, making Indemnification Agreement To The Surety, and create a reinsurance agreement (re-insurance). (2) As a result of Law Arising in the Implementation of Default Occurs When Surety Bond in PT Askrindo on Procurement Project in Surakarta City Government recovery billing is done directly by sending a letter to the Principal for immediate execution of collateral that is the Surety. Barriers Faced Surety Company In Subrogation or Recovery Implementation is: Principal inability to meet achievement at the obligee; Not optimal results obtained Surety Company in the implementation of subrogation or recovery, due to lack of ability Principal thus freed Surety Company of costs incurred and interest to be paid. Therefore PT. Askrindo give leeway to the Principal to perform subrogation or recovery in installments and release of costs incurred and interest to be paid.